2018
DOI: 10.3389/fneur.2018.00437
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Stenosis Contralateral to Intracranial Large Vessel Occlusion: An Independent Predictor of Unfavorable Clinical Outcome After Mechanical Thrombectomy

Abstract: Background: Clinical outcome in patients undergoing mechanical thrombectomy (MT) due to intracranial large vessel occlusion (LVO) in the anterior circulation is influenced by several factors. The impact of a concomitant extracranial carotid artery stenosis (CCAS) contralateral to the intracranial lesion remains unclear.Methods: Retrospective analysis of 392 consecutive patients treated with MT due to intracranial LVO in the anterior circulation in two comprehensive stroke centers between 2014 and 2017. Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Even though our study lacks a control cohort of patients without surgery, data in the litrature suggest that contralateral stenosis has a negative impact regardless of additional procedures such as CAS or CEA: Maus et al compared straight-forward thrombectomy stroke patients with and without contralateral stenosis (>50%) and found that contralateral stenosis was independently associated with significantly larger infarctions (176 cm 3 vs 11 cm 3 ; P < .001) and unfavorable outcome (93% vs 65%; P = .003). 14 This suggests that a complete CoW should have a protective impact on outcome, which was shown to be the case in some studies, but which was not the case in our study and the study of Seifeld-Held et al [23][24][25] Because most patients in our cohort had an incomplete circle of Willis, more comprehensive studies are needed to develop a full picture of this issue. Regarding intraoperative shunting, our results do not speak for or against its use, especially because the use of a shunt was not randomized but at the surgeons' discretion in our study.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Even though our study lacks a control cohort of patients without surgery, data in the litrature suggest that contralateral stenosis has a negative impact regardless of additional procedures such as CAS or CEA: Maus et al compared straight-forward thrombectomy stroke patients with and without contralateral stenosis (>50%) and found that contralateral stenosis was independently associated with significantly larger infarctions (176 cm 3 vs 11 cm 3 ; P < .001) and unfavorable outcome (93% vs 65%; P = .003). 14 This suggests that a complete CoW should have a protective impact on outcome, which was shown to be the case in some studies, but which was not the case in our study and the study of Seifeld-Held et al [23][24][25] Because most patients in our cohort had an incomplete circle of Willis, more comprehensive studies are needed to develop a full picture of this issue. Regarding intraoperative shunting, our results do not speak for or against its use, especially because the use of a shunt was not randomized but at the surgeons' discretion in our study.…”
Section: Discussionmentioning
confidence: 48%
“…All common thrombectomy techniques such as stent-retriever thrombectomy, ADAPT (A Direct Aspiration First Pass Technique) and combined approaches such as SAVE (Stent-Retriever Assisted Vacuum-Locked Extraction) and Solumbra (use of a stent retriever with concomitant distal aspiration) are established in our clinic. 14 We implemented an interdisciplinary consensus in our hospital to perform thrombectomy with general anesthesia and to avoid CAS whenever possible and to perform CEA in the same anesthesia session in our angiography suite either before or after thrombectomy whenever necessary. For this, we notify our vascular surgery team, which is available 24/7, whenever 1) surgical access to the occlusion site is needed because access to the occlusion site via femoral or radial/brachial access is expected to be difficult and to take longer than 45 minutes or 2) CAS and DAPT should be avoided in a case of high-grade ICA stenosis.…”
Section: Clinical Proceduresmentioning
confidence: 99%
“…A favourable clinical outcome at follow-up correlated significantly with a younger age, a more peripheral intracranial vessel occlusion, and good intracranial collaterals. The latter feature is known to play a crucial role in stroke treatment in general, as the existence or absence of intracranial collaterals does directly influence the size of the infarct core, the tissue at risk (penumbra), and a potential time window until successful recanalization [10][11][12][13]. It is therefore not surprising, that the grade of intracranial collateralisation had an impact on clinical outcome in our patients, as the treatment is more complex and often more time consuming than in "simple" thrombectomy.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, few currently published investigations have attempted to clarify the role of contralateral carotid stenosis (CCS). Higher mortality in AIS patients with a CCS > 50% and an ipsilateral patent carotid artery has been observed ( 3 , 4 ). The presence of significant CCS in patients with severe ICS was found to be an independent risk factor for acute cerebral vascular impairment with a 3-fold higher risk of TIA or stroke ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of ICS in AIS varies between 15 and 20% of cases ( 2 ), while data on CCS are lacking: some studies have estimated an incidence of 9% ( 3 ). Furthermore, few data are available on the different impacts of ICS and CCS on interventional therapies for AIS.…”
Section: Introductionmentioning
confidence: 99%